The Socialization of Women Administrators In Education: How Can They Fit in? - P. Kay Duncan (Educational Considerations, 1995)
The expectations of others for a female administrator can be extraordinary and even the woman administrator's self-imposed aspirations can be formidable...it becomes apparent that a female must undergo socialization or training not only as an administrator, but more specifically as a "woman" administrator.